Penguatan Tata Kelola Bengkel melalui Pelatihan K3, Implementasi SOP, dan Optimalisasi Toolset di Bengkel Nandar Automotive - Susi Tri Umaroh; Sudirman Rizki Ariyanto; Ferly Isnomo Abdi; Warju Warju; Lailatus Sa'diyah Yuniar Arifianti; Yustin Setiya Widoretno (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
This community service program was implemented to strengthen the operational governance of Nandar Automotive Workshop, which faces several fundamental issues, including limited knowledge of occupational health and safety (OHS), absence of documented Standard Operating Procedures (SOPs), and insufficient ergonomic toolsets. The program aimed to improve workplace safety, standardize service procedures, and enhance repair productivity through K3 training, SOP development, and optimized tool usage. The implementation involved needs assessment, training sessions, mentoring, and evaluation using pre–post testing, observation checklists, and time-efficiency measurements. The results showed a substantial improvement in participants’ understanding of OHS, with average scores increasing from 50% to 80%. SOP compliance also increased significantly, from 30% to 83%, following structured socialization and mentoring. Toolset optimization reduced the average service time from 63 minutes to 50 minutes, increasing work efficiency by 21%. These achievements indicate that integrating competency development, standardized procedures, and ergonomic tools effectively enhanced organizational performance and the safety culture at the partner workshop. Follow-up recommendations include continuous mentoring, adoption of digital service records, and advanced diagnostic training to strengthen the workshop’s long-term competitiveness.